Arthur's prize reader - Hoban, Lillian (New York : Harper & Row, 1978)
Although Arthur loses the Super Chimp Club contest, his pupil, sister Violet, wins the first grade reading competition and a prize for them both.
School Library Journal
Booklist
Horn Book
2.0
K-3.
Keywords: Brothers and sisters -- Fiction; Reading -- Fiction; Reading -- Fiction; Siblings -- Fiction